2014
DOI: 10.5194/acp-14-8905-2014
|View full text |Cite
|
Sign up to set email alerts
|

Air–sea exchange and gas–particle partitioning of polycyclic aromatic hydrocarbons in the Mediterranean

Abstract: Polycyclic aromatic hydrocarbon (PAH) concentration in air of the central and eastern Mediterranean in summer 2010 was 1.45 (0.30-3.25) ng m −3 (sum of 25 PAHs), with 8 (1-17) % in the particulate phase, almost exclusively associated with particles < 0.25 µm. The total deposition flux of particulate PAHs was 0.3-0.5 µ g m −2 yr −1 . The diffusive air-sea exchange fluxes of fluoranthene and pyrene were mostly found net-depositional or close to phase equilibrium, while retene was net-volatilisational in a large … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 61 publications
3
24
0
Order By: Relevance
“…The minimum concentrations were measured offshore in T 3-3(1) , T 6-8 and T 8-9 . Concentrations presented in this work were for most PAHs lower than those found previously in the Black and Eastern Mediterranean Sea (CastroJimenez et al, 2012;Tsapakis and Stephanou, 2005), Pacific and Atlantic Oceans (Xu et al, 2012;Nizzetto et al, 2008;Del Vento and Dachs, 2007); on the other hand, our values were in agreement with data reported for Indian Ocean air (Liu et al, 2014) and Mediterranean sub-basins (Castro-Jim enez et al, 2012), as well as with cruise measurements performed in the south-eastern Mediterranean in summer 2010 (Mulder et al, 2014). The seasonality of emissions, the different maritime traffic in these regions or its combination with various cruise routes distinctly influenced by in land combustion sources on land (biomass burning, power plants etc.…”
Section: Pah Concentrationssupporting
confidence: 92%
See 1 more Smart Citation
“…The minimum concentrations were measured offshore in T 3-3(1) , T 6-8 and T 8-9 . Concentrations presented in this work were for most PAHs lower than those found previously in the Black and Eastern Mediterranean Sea (CastroJimenez et al, 2012;Tsapakis and Stephanou, 2005), Pacific and Atlantic Oceans (Xu et al, 2012;Nizzetto et al, 2008;Del Vento and Dachs, 2007); on the other hand, our values were in agreement with data reported for Indian Ocean air (Liu et al, 2014) and Mediterranean sub-basins (Castro-Jim enez et al, 2012), as well as with cruise measurements performed in the south-eastern Mediterranean in summer 2010 (Mulder et al, 2014). The seasonality of emissions, the different maritime traffic in these regions or its combination with various cruise routes distinctly influenced by in land combustion sources on land (biomass burning, power plants etc.…”
Section: Pah Concentrationssupporting
confidence: 92%
“…These investigations were focused on both macro and micro-components, inorganic and organic substances, gaseous compounds, semi-volatile and particulate species. Nevertheless, rather than to marine air attention was overall paid to sea water (dissolved and suspended materials: Maldonado et al, 1999;Campanelli et al, 2004;Nizzetto et al, 2008;Berrojalbiz et al, 2011;Castro-Jim enez et al, 2012;Marrucci et al, 2013;Siemers et al, 2015), sediments (Gogou et al, 2000;Tsapakis et al, 2006;Cardellicchio et al, 2007;Perra et al, 2011;Acquavita et al, 2012Acquavita et al, , 2014Marini and Frapiccini, 2013;Net et al, 2015) and sea/air interface (Marty et al, 1988;Manodori et al, 2006;Lohmann et al, 2009;Guitart et al, 2010;Mulder et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…However, air-sea exchange of POPs is controlled by the combination of the parameters temperature, wind speed and concentration in surface water (Stemmler and Lammel 2011). Moreover, it has been observed that the direction of air-sea exchange may fluctuate once the substance concentration has approached (or is close to) phase equilibrium on a range of time scales (Jantunen and Bidleman 1995; Stemmler and Lammel 2009; Berrojalbiz et al 2014; Mulder et al 2014; Lammel et al 2016). This could explain these observations.…”
Section: Resultsmentioning
confidence: 99%
“…Anthropogenic PAHs are omnipresent in environmental matrices and are found in the atmosphere, soil, water, ice, sediment, and food web [ Chen et al ., ; C. Wang et al ., ; Lohmann et al ., ; Yuan et al ., ; Stout and Graan , ; Huang and Batterman , ], due to the global distribution of sources and the resistance of PAHs to degradation. Marine sediments usually act as important sinks for anthropogenic PAHs through two major pathways, riverine discharge and atmospheric deposition [ Wang et al ., ; Mulder et al ., ; González‐Gaya et al ., ]. Following release into the marine environment, most PAHs bind to fine particles, due to their high hydrophobicity and lipid solubility, and are deposited in the bottom sediments.…”
Section: Introductionmentioning
confidence: 99%